The Command Center as a Data and Information Control in Tenggarong Seberang Kutai Kartanegara - Muhammad Arif Nurrahman; Kus Indarto; Friska Prastya Harlis; Audya Dewintha (Rumah Jurnal, University of Jember, 2025)
The Command Center is a breakthrough made by the Tenggarong Seberang District to improve public services as a Data and Information Center to support government programs related to Satu Data Indonesia (SDI) at the sub-district level. This command center aims to make it easier to obtain data and information that is useful for planning the development of Kutai Kartanegara Regency. This was done because, so far, the data collected by the sub-district has not been properly documented digitally. This method will make data in the sub-district easier to access and search when needed. This research aims to analyze the implementation of the command center in Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan. To realize the successful implementation of the command center, Tenggarong Seberang District has made breakthroughs in the form of providing facilities and infrastructure, providing quality human resources, building cooperation with all UPT heads and village heads, collecting potential information data and inputting data and information into the application system. Owned by the district. The research results show that implementation has gone well. This can be seen through the stages that have been carried out